1998
DOI: 10.1016/s0741-5214(98)70166-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of spinal cord ischemia by selective intercostal arterial infusion of prostaglandin E1

Abstract: In this model, PGE1 administration at the rate of 50 ng/kg/min showed sufficient spinal cord protection against ischemia without a decrease in the blood pressure. Further studies are needed to determine the dose that will provide the maximal protective effect and to determine the maximum duration of ischemia against which PGE1 shows protective effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Clarification of such mechanisms to prevent this surgical complication or at least to prevent functional deficit progression to the permanent delay-onset paraplegia would be of the highest value. Despite reduction of postoperative paraplegia incidence in recent years using surgical modifications such as temporary shunts and hypothermia [12], and pharmacological approaches including free radical scavengers [6], NMDA receptor antagonists [13] and vasodilators [14], this surgical complication has not yet been totally eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…Clarification of such mechanisms to prevent this surgical complication or at least to prevent functional deficit progression to the permanent delay-onset paraplegia would be of the highest value. Despite reduction of postoperative paraplegia incidence in recent years using surgical modifications such as temporary shunts and hypothermia [12], and pharmacological approaches including free radical scavengers [6], NMDA receptor antagonists [13] and vasodilators [14], this surgical complication has not yet been totally eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In many SCI animal protocols, the aorta is cross-clamped to interrupt intercostal or lumbar arterial perfusion, because the small aortic branches are so numerous and ligating or clamping them is complicated. In canine SCI experimental models, the thoracic aorta is occluded in a manner mimicking the operative condition.…”
Section: Discussionmentioning
confidence: 99%
“…As documented in the previous reports on SCI experiments using dogs, aortic cross-clamping alone (CL) or aortic occlusion associated with proximal-to-distal aortic bypass (CL-AB) has been performed to induce ischemia. [1][2][3][4][5] We think that our new technique has several advantages over these two methods. Unlike CL, our method makes it possible to lower the PAP to the targeted level and to inhibit the initial rise in the PAP during cross-clamping.…”
Section: Discussionmentioning
confidence: 99%
“…The latter may worsen spinal cord ischemia by decreasing the perfusion pressure. Many interventions have been proposed to prevent the consequences of aortic occlusion, including distal aortic perfusion [4], CSF drainage [5], hypothermia [6], production of heat shock proteins by preconditioning procedures [7,8], and pharmacological agents such as oxygen-free radical scavengers [9], iron chelators [10], N-methyl-D-asparate (NMDA) receptor antagonists [11,12], opiate antagonists [13], and vasodilators [14]. A number of studies have reported beneficial effects of these interventions, but most of them remain controversial.…”
mentioning
confidence: 99%
“…Our current results confirm that systemic, mild hypothermia is a safe and effective neuroprotective method during ischemiareperfusion injury of the spinal cord. [Japanese Journal of Physiology, 53, [9][10][11][12][13][14][15]2003] Rabbits have been used widely as an animal model for spinal cord ischemia-reperfusion injury after aortic aneurysm repair because of their unique segmental arterial blood supply to the spinal cord through lumbar arteries (L4-L6) arising from the infrarenal aorta [15]. Therefore, aortic occlusion using a balloon catheter at the infrarenal aorta results in spinal cord ischemia in the rabbit.…”
mentioning
confidence: 99%